Deslocamentos pendulares e a saúde do trabalhador: uma análise dos processos e percursos diários para Macaé - RJ - Pinheiro, Sílvia Regina Teodoro (2019)
The thesis aims to study the repercussions, impacts and consequences on the health of workers on commuting, on the routes, on the daily routes in the coastal lowland towards Macaé, the agglutinative city of the labor market of the petroleum industry. The object studied is the workers who live along the coastal shoreline and move, for the most part, to work in on and off shore companies. The main objectives were: to verify the consequences of the displacements in the health process; identify socioeconomic conditions, health, social determinants of health; to prove that the targets of capitalist accumulation, by concentrating profits, end up reproducing an imbalance in the quality of life and in the well-being of the workers. Method: a cross-sectional synchronous study was carried out during 2016 to 2018. It was developed in two phases: the first one refers to the delimitation, planning and dialogues of protocol negotiations with the institutions involved, in compliance with Resolution 466 of 12 December 2012: the second refers to the application of a questionnaire with the workers' population, in the itinerant process in the chartered buses, in the post-return of a working day. The study was submitted to the Ethics and Research Committee of PUC-SP, approved under protocol nº CAAE 72948317.9.00005482. Among the main results, social issues, gender differences and inequalities have been observed: women on the way to work have, above all, preoccupations with family members who stay at home. In the health history, the predominant data for overweight and alcoholic beverages were observed. In the pendular displacement for work, the questions of sleep and physical fatigue were identified. Discussion: analysis of environmental resources in the coastal lowland region, maps, routes, regions and microregions of health, occupational health concerns should occur in the planning of intersectoral public policies, in promoting collective health surveillance. Final considerations: the human consequences, caused by the impact inside and outside the work environment, with a risk to the health of the workers, are due to the lack of integration in the planning of the public and private policies for workers within the scope of the Unified Health System, the National Health Policy for Workers, and the Urban Mobility Policy